Pengaruh Stres Kerja Terhadap Kinerja Pegawai Pada Dinas Pendidikan Dan Kebudayaan Kabupaten Aceh Tengah - Jalil. M., Abd.; Sabri, Sabri; Panea, Yolanda Riyan (Universitas Gajah Putih, 2024)
This research aims to determine the effect of work stress on employee performance. The population of this study were employees of the Central Aceh Regency Education and Culture Office, totaling 67 people. Sampling uses a saturated sampling technique, namely a sampling technique when all members of the population are used as samples. Data collection uses techniques through observation instruments, interviews, questionnaires and documentation, then the data is processed, presented and analyzed using simple linear regression methods and hypothesis testing, namely partial statistical tests (t-test) and determination tests (R²). The research results show a regression equation, where: , correlation and . Partially, the work stress variable (X) has a negative and significant effect on employee performance (Y) with a t value = - 2.020 t table of 1.997 with a significance of 0.047 < 0.05. This data shows that the higher an employee's work stress, the lower the employee's performance will be, conversely, the lower the employee's work stress, the greater the impact on employee performance at the Central Aceh District Education and Culture Service. The test results for the coefficient of determination were 0.552 or 55.2%, meaning that 55.2% of employee performance was influenced by the independent variable (Job Stress). Meanwhile, the remaining 44.8% is influenced by other factors such as work environment, job training, career development, leadership style, etc.